2015
DOI: 10.1097/igc.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Early Detection of Postpartum Choriocarcinoma

Abstract: The most common symptom of patients with postpartum choriocarcinoma in the short and long interval groups was genital bleeding, and the overall prognosis may be improved by introduction of an appropriate chemotherapy regimen. Careful pathological examination of the placenta is needed in cases of fetomaternal hemorrhage, unknown fetal anemia, and abnormal obstetric events, including premature delivery, still birth, and infantile growth retardation, for the early detection of intraplacental choriocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Second, only a single gestational sac and fetus were confirmed at the early pregnancy, and the cervical tumor could not be detected during the first trimester. Third, the interval between the precedent abortion and the onset of first bleeding was approximately 11 months; thus, our patient fits into the long‐interval category suggested by Ryu et al …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Second, only a single gestational sac and fetus were confirmed at the early pregnancy, and the cervical tumor could not be detected during the first trimester. Third, the interval between the precedent abortion and the onset of first bleeding was approximately 11 months; thus, our patient fits into the long‐interval category suggested by Ryu et al …”
Section: Discussionsupporting
confidence: 67%
“…Ryu et al reported on two groups of post‐partum choriocarcinoma, consisting of short‐ and long‐interval groups in which patients had symptomatic onset after less than 5 months and more than 11 months, respectively . In the short‐interval group, choriocarcinoma was considered to have developed from an intraplacental choriocarcinoma, whereas in the long‐interval group, retained villous tissue of the previous pregnancies, including abortion and molar pregnancy, was considered the source . In the present case, although there was no clear evidence to explain which theory would be most accurate (data about the placental pathology and intrauterine content of the first pregnancy were lacking), our patient might have experienced a gestational choriocarcinoma, which would be consistent with the third theory.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Doctors are skeptical about using chemotherapy for patients where no evidence of the disease is found after delivery. In most gestational choriocarcinoma cases identified soon after delivery, the metastatic tumor was detected within 2 months of the last delivery . Thirty‐one previous cases without maternal disease within 2 months of the last delivery have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In most gestational choriocarcinoma cases identified soon after delivery, the metastatic tumor was detected within 2 months of the last delivery. 13 Thirty-one previous cases without maternal disease within 2 months of the last delivery have been reported. Of these, chemotherapy was administered in just four cases, and dilatation and curettage was performed in just three cases although no metastatic tumor was detected.…”
Section: Discussionmentioning
confidence: 99%